Rasionalitas Simbol Dan Komunikasi Dalam Perpektif Teori Exchange Dalam Ilmu Sosial Kontemporer - Siti Ayu Nuriana; Mohammad Rofiq (4, 2026)
This study aims to analyze the rationality of symbols and communication from the perspective of Exchange Theory as a relevant theoretical framework for understanding the dynamics of social interaction in contemporary social science. Based on the assumption that social action is not solely driven by material interests, this study emphasizes the importance of the symbolic and communicative dimensions in the social exchange process. A qualitative approach was employed, employing library research on classical and contemporary works by social scientists discussing Exchange Theory, social rationality, symbols, and communication. The data obtained were analyzed using conceptual and interpretive analysis techniques to uncover the dialectical relationship between social exchange, symbolic meaning, and the communication process in social action. The results of the study indicate that Exchange Theory cannot be understood reductively as merely material exchange but also encompasses symbolic exchanges imbued with values, meaning, recognition, and social legitimacy. Rationality in this context is multidimensional, encompassing interrelated and interdependent economic, social, and symbolic aspects. These dimensions of rationality are expressed and negotiated through communication, which serves as the primary mechanism for building trust, conveying symbols, and negotiating interests and meanings in social relations. In the context of modern society and contemporary digital space, communication has become increasingly complex yet remains central to maintaining the sustainability of social relations. This study confirms that the integration of symbolic rationality and communication strengthens the relevance of Exchange Theory as an adaptive, contextual theoretical framework capable of explaining the complexity of modern social dynamics by considering cultural factors, social structures, and technological developments. Abstrak Kajian ini bertujuan untuk menganalisis rasionalitas simbol dan komunikasi dalam perspektif Teori Exchange sebagai kerangka teoretis yang relevan untuk memahami dinamika interaksi sosial dalam ilmu sosial kontemporer. Berangkat dari asumsi bahwa tindakan sosial tidak semata-mata didorong oleh kepentingan material, penelitian ini menekankan pentingnya dimensi simbolik dan komunikatif dalam proses pertukaran sosial. Pendekatan kualitatif digunakan dengan metode studi literatur (library research) terhadap karya-karya klasik dan kontemporer para ilmuwan sosial yang membahas Teori Exchange, rasionalitas sosial, simbol, serta komunikasi. Data yang diperoleh dianalisis melalui teknik analisis konseptual dan interpretatif guna mengungkap hubungan dialektis antara pertukaran sosial, makna simbolik, dan proses komunikasi dalam tindakan sosial. Hasil kajian menunjukkan bahwa Teori Exchange tidak dapat dipahami secara reduktif sebagai pertukaran material semata, melainkan juga mencakup pertukaran simbolik yang sarat dengan nilai, makna, pengakuan, dan legitimasi sosial. Rasionalitas dalam konteks ini bersifat multidimensional, meliputi aspek ekonomi, sosial, dan simbolik yang saling terkait dan saling memengaruhi. Dimensi rasionalitas tersebut diekspresikan dan dinegosiasikan melalui komunikasi, yang berfungsi sebagai mekanisme utama dalam membangun kepercayaan, menyampaikan simbol, serta menegosiasikan kepentingan dan makna dalam relasi sosial. Dalam konteks masyarakat modern dan ruang digital kontemporer, komunikasi menjadi semakin kompleks namun tetap berperan sentral dalam menjaga keberlanjutan hubungan sosial. Kajian ini menegaskan bahwa integrasi rasionalitas simbol dan komunikasi memperkuat relevansi Teori Exchange sebagai kerangka teoretis yang adaptif, kontekstual, dan mampu menjelaskan kompleksitas dinamika sosial modern dengan mempertimbangkan faktor budaya, struktur sosial, dan perkembangan teknologi.